Tuberculosis in Children and BCG Vaccination in North Sumatra - Jo Kian Tjay; Robencius Saragih; Sahat Halim; Tjut Irawati; P. Harnopidjati; S.M. Manoeroeng; M.V.O. Sitompul (Indonesian Pediatric Society, 1975)
Data of child tuberculosis, clinical visits and those who were treated in the three hospitals, visits to the 6 public health centers (Puskesmas) and figures of BCG immunization in the North Sumatra Province were presented.Although the tuberculin index in children in Medan (1965) was lower than that in Java (BCG Mass Campaign, 1954 - 1964), primary tuberculosis patients treated in the General Hospital (RSUPP) constituted 1.14% of the total patients admitted to the hospital in 1963 - 1972, whereas in the â€PNP IXâ€ hospital it was 0.84%. From a survey of families (1962 - 1969) it revealed that infection in the families was Â± 50%. While 76.1% of the meningitis patients were under the age of 4 years. From a survey of 6 public health centers we found through a Pilot Project that 1.02% patients had a positive sputum. The above mentioned figures gave the indication that BCG immunization had to be performed in children under the age of 4 years. However, the figures of the BCG campaign (1970 - 1973) at the above mentioned Pilot Project revealed that coverage in the under 5 - years - old age was 20.5%, whereas in the 5 - 14 years age group it was 49.2%.In practice the realization of massal BCG immunization was certainly the simplest with school age children who were already grouped and registered; nevertheless, partly of them hai already got infected and had been released from tuberculous meningitis complication. BCG immunization as mentioned above (probably it was also given mother areas in Indonesia) did obviously not reach its right target.